Impact of advanced liver fibrosis on atrial fibrillation recurrence after ablation in non-alcoholic fatty liver disease patients - Wang, Zhe; Wang, Yijia; Luo, Fangyuan; Zhai, Yafei; Li, Jiaju; Chen, Yinong; Li, Qing; Zhu, Longyang; Jiao, Siqi; Liu, Peng; Zhou, Yifeng; Chen, Yingwei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aim Advanced liver fibrosis is independently associated with new onset of atrial fibrillation (AF). Non-invasive liver fibrosis scores are considered an effective strategy for assessing liver fibrosis. This study aimed to investigate the association between advanced liver fibrosis and AF recurrence after ablation in patients with non-alcoholic fatty liver disease (NAFLD). Materials and methods A total of 345 AF patients with NAFLD who underwent de novo ablation between 2019 and 2020 at two large hospitals in China were included in this study. AF recurrence was defined as the occurrence of atrial arrhythmia for more than 30 s by electrocardiogram or 24 h Holter monitoring after the first 3 months of ablation. Predictive values of non-alcoholic fatty liver disease fibrosis score (NFS) and Fibrosis-4 (FIB-4) scores for AF burden and recurrence after ablation were assessed. Results At the 1 year follow-up after ablation, 38.8% of patients showed recurrence. Patients with recurrence who had higher FIB-4 and NFS scores were more likely to have persistent AF and a duration of AF ≥ 3 years. In Kaplan–Meier analysis, patients with intermediate and high NFS and FIB-4 risk categories had a higher risk of AF recurrence. Compared to patients with the low risk, intermediate and high NFS, and FIB-4 risk were independently associated with AF recurrence in multivariate Cox regression analysis (high risk: NFS, hazard ratio (HR): 3.11, 95% confidence interval (CI): 1.68∼5.76, p < 0.001; FIB-4, HR: 3.91, 95% CI: 2.19∼6.98, p < 0.001; intermediate risk: NFS, HR: 1.85, 95% CI: 1.10∼3.10, p = 0.020; FIB-4, HR: 2.08, 95% CI: 1.27∼3.41, p = 0.003). Conclusion NFS and FIB-4 scores for advanced liver fibrosis are associated with AF burden. Advanced liver fibrosis is independently associated with AF recurrence following ablation. Advanced liver fibrosis might be meaningful in risk classification for patients after AF ablation.